2012
DOI: 10.1124/jpet.111.190900
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Antigen Specificity of T-Cell Clones from Piperacillin-Hypersensitive Patients with Cystic Fibrosis

Abstract: ␤-Lactam antibiotics provide the cornerstone of treatment and reduce the rate of decline in lung function in patients with cystic fibrosis, but their use is limited by a high frequency of delayedtype allergic reactions. The objective of this study was to use cloned T-cells expressing a single T-cell receptor from five piperacillin-hypersensitive patients to characterize both the cellular pathophysiology of the reaction and antigen specificity to define the mechanism of activation of T-cells by piperacillin. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 28 publications
4
100
3
1
Order By: Relevance
“…Interestingly, the b-lactam antibiotics piperacillin, amoxicillin, and penicillin G, which bind to similar albumin lysine residues, also stimulated the flucloxacillinresponsive clones. The detection of broadly crossreactive T cells is in contrast to our recent studies describing highly drug-specific T cells in piperacillin-hypersensitive patients, 14 and suggests that MHC binding peptides and the core penicilloyl structure provide the binding energy to drive T-cell responses in patients with flucloxacillin-induced liver injury.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Interestingly, the b-lactam antibiotics piperacillin, amoxicillin, and penicillin G, which bind to similar albumin lysine residues, also stimulated the flucloxacillinresponsive clones. The detection of broadly crossreactive T cells is in contrast to our recent studies describing highly drug-specific T cells in piperacillin-hypersensitive patients, 14 and suggests that MHC binding peptides and the core penicilloyl structure provide the binding energy to drive T-cell responses in patients with flucloxacillin-induced liver injury.…”
Section: Discussioncontrasting
confidence: 66%
“…Using mass spectrometric methods, we recently identified albumin as a major circulating protein modified with b-lactam antibiotics including flucloxacillin, defined the profile of drug protein conjugation at specific lysine residues with respect to dose and incubation time, and characterized for the first time the sites of modification associated with the stimulation of a clinically relevant drug-specific T-cell response. 13,14,16 Herein, we show that (1) the stimulation of clones with flucloxacillin-pulsed antigen-presenting cells, and (2) the detection of flucloxacillin haptens on albumin in culture are time-dependent. Furthermore, simultaneous measurement of antigenicity and immune responsiveness revealed that the cumulative level of flucloxacillin protein binding at each timepoint studied correlated directly with the strength of the T-cell proliferative response.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations